Product Quality Improvement in the Assembly Process of the 5.56 mm Ammunitions (Variant MU5-TJ) at PT.X Using the Six Sigma Method - Ratna Sari Trisna Wardani; Mokhamad Suef (Institut Teknologi Sepuluh Nopember, 2020)
Quality is one of the essential indicators for companies to exist amid strong competition. The 5.56 mm ammunition, especially variant MU5-TJ, is the primary commodity of PT. X. The process in ammunition production includes making cartridge cases, making bullets, making primers, and assembling ammunitions. The highest cost of defective products is led by defects in the preparation of the 5.56 mm ammunition, reaching 32.3%. In the process of preparing this kind of ammunition, most of the defects came from variant MU5-TJ, which accounted for 64%. This study aimed to improve the quality of the MU5-TJ ammunition preparation process by increasing its level of sigma. The method used in this study was the Six Sigma method through the Define, Measure, Analyze, Improve, and Control (DMAIC) phases. The quality identification results showed that the weighing and gauging process was the most contributing factor to the defects in the preparation of MU5-TJ ammunitions. The main defect found was the improper weight of the munitions due to the underfilling of propellant powder. The results of the chi-square test showed that the defect-causing factors with significant effects included the presence of sensor filling, varnish composition, tool material, and inspection methods. To reduce the defects, further improvements were made by installing the filling sensor on the ammunition assembly machine, changing the composition of the cartridge case mouth varnish, the use of tools made of hartmetall, and auto-control by the operator every 15 minutes. The results of the implementation of the improvements made resulted in an increase in sigma level from 3.69 to 3.79.